Meningkatkan Pemahaman Peserta Didik Kelas IV Dengan Metode PBL Berbantuan Video Pembelajaran di SDN 071060 Kabupaten Nias - Deliana Hondro; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study, titled "Improving the Understanding of Grade IV Students with the PBL Method Assisted by Learning Videos at SDN 071060 Nias Regency," was motivated by the low level of student understanding that hindered effective learning outcomes. The research aimed to determine whether the Problem-Based Learning (PBL) method supported by instructional videos could enhance students’ comprehension of subject matter. A Classroom Action Research (CAR) approach was implemented over two cycles, with each cycle comprising the stages of Planning, Action, Observation, and Reflection. Data were collected through observations and test results. In the first cycle, only 42.85% of students reached the "Proficient" category, indicating limited understanding. However, in the second cycle, there was a significant improvement, with 100% of the students attaining the "Proficient" level, demonstrating strong comprehension of the material presented. These findings suggest that the integration of PBL and learning videos can effectively improve learning outcomes, especially in enhancing students’ critical thinking and understanding. It is recommended that educators adopt the PBL method supported by visual learning aids such as videos to foster a more interactive and engaging learning experience. This approach can be a strategic alternative in overcoming students’ difficulties in grasping complex concepts and in promoting active participation in the classroom.